Developing speech assistive tools for neurofeedback training - William, Osvera Bella (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Speech assistive tools are devices that help to enhanced children who are having a speech delay problem. In this research, we developed a video speech toolkit that could help to enhance the children speech. This study aims to determine the effectiveness of the speech assistive tools in enhancing speech delay. The purpose of this study is to prove that there is improvement in participant's speech after they undergoes several neurofeedback training using the video speech toolkit. During training, participants were asking to watch and learn according to the video speech toolkit, sing along while watch several video songs, and play the neurofeedback games to train their relaxation during play. Both participants shows an immense improvement in their speech and also changes in their behaviour during the neurofeedback training. Both participants were also able to focus and give full attention during the training which can be seen on their Electroencephalogram (EEG) neurofeedback result.